PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG DENGAN MENGGUNAKAN METODE FIRST IN FIRST OUT (FIFO) DI PT INDAH KIAT PULP AND PAPER PRODUCT - Sutanto Sutanto; Irma Yunita Ruhiawati; Anggi Rizki Damas (Journal of Innovation And Future Technology (IFTECH), 2021)
During the process of supply of goods there has not been monitoring for the supply of goods, incoming goods, outgoing goods, stock items, as well as double item data, and difficult in finding inventory data. There fore it is necessary to make a system and the right method to manage the problem of inventory of goods in Indah Kiat Pulp and Paper Product Inc. The method used to solve this problem is the FIFO (First in First Out) which is a method of determining inventory based on the assumption that the goods that are first obtained / bought (entered) are the first to be sold or issued. Thus the goods in inventory are considered to be from the last purchases, because the goods from the previous purchase are considered to have been sold or released so that later the method will be combined in a system designed in the form of DFD to monitor inventory of goods as mentioned in the problem above and the method used to develop the system is the waterfall model and the programming language used to create the website, PHP and for example as the database.